Metal-doped CdS/MoS2 heterojunctions for photocatalytic degradation of organic pollutant. (15th June 2022) - Karamoschos, Nikolaos; Bairamis, Feidias; Andrikopoulos, Konstantinos S.; Konstantinou, Ioannis; Tasis, Dimitrios
Abstract: The present work describes the synthesis of metal-doped CdS/MoS2 heterojunctions, prepared by a two-step microwave-assisted solvothermal approach. The samples were characterized by X-ray diffraction spectroscopy (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Raman analysis as well as diffuse reflectance spectroscopy (DRS). The photocatalytic activity was assessed against the decomposition of 4-nitrophenol, in the presence of oxalic acid as sacrificial agent. At macroscopic scale, the hybrids demonstrated a certain level of phase separation, implying an inhomogeneous distribution of cocatalyst nanoparticles within the main semiconductor matrix. XPS analysis revealed that the main molybdenum-based species found was MoS2, whereas MoO3 was formed also. DRS measurements showed an actual shift of the absorption edge of hybrids, when compared with the corresponding one of bare CdS nanoparticles. The different photocatalytic activities may be attributed to differences in the relative population of heterojunctions and to the variable ratio of the molybdenum-based species (disulfide/trioxide) within each hybrid. Comparison with analogous studies suggests that the chemical speciation of the third component is critical towards the development of photocatalytic systems carrying a large population of heterojunctions.